Determination and Classification of Explosive Atmosphere Zones While Considering the Height of Discharges - Mihoub, Zakarya; Ouslati, Ahmed; Hacene Smadi; May, Bilal (Journal of Failure Analysis and Prevention, 2020)
Prevention and protection of explosions are two notions often used subjectively, and to transform them into operative terms of decision support, it is indispensable to develop quantitative or semiquantitative approaches to determine the hazardous zones. The “classical and point-source” approaches that determine ATEX (explosive atmospheres) zones are semiquantitative methods that can meet the requirements of the ATEX directives (Directives 99/92/EC and 94/9/EC). The methodology’s principle in determining ATEX zones consists in making a comparison with typical examples “classical approach” and to identify the source points, determine the degree of discharge, identify the type of the zone, determine the radius of the zone and ultimately the extent and shape of this zone “source point approach.” The aim of this work is, on the one hand, to propose and present a classification methodology of the ATEX zones and, on the other hand, to apply the proposed methodology in a hydrocarbon separator.